2022
DOI: 10.3390/ani13010111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extenders Supplementation with Gum Arabic and Antioxidants on Ram Spermatozoa Quality after Cryopreservation

Abstract: Semen cryopreservation is very important in animal agriculture to maximize the number of daughters of genetically superior males and to distribute the cryopreserved semen of good males all over the world. However, the freezing process generates some damage to sperm that reduce their fertilizing ability after thawing. Moreover, egg yolk, which is the most common animal-origin cryoprotectant used in semen dilution, is considered a source of biosecurity risk. In the current study, we aimed to compare the replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
1
1
Order By: Relevance
“…However, our findings are against those of Shehab‐El‐Deen et al. (2023), who did not observe any significant difference in acrosome integrity at any of the concentrations of gum arabic, a polysaccharide. Although the mechanism is unclear, the difference in acrosome integrity can be attributed to the structural differences and their interaction with cellular components.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our findings are against those of Shehab‐El‐Deen et al. (2023), who did not observe any significant difference in acrosome integrity at any of the concentrations of gum arabic, a polysaccharide. Although the mechanism is unclear, the difference in acrosome integrity can be attributed to the structural differences and their interaction with cellular components.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, only some pertinent research papers are reported concerning the application of k-carrageenan oligosaccharides in the cryopreservation of gametes. Supplementation of k-carrageenan oligosaccharide in the semen extender of rooster and canine sperm showed improved post-thaw quality (Chung et al, 2003;Shehab-El-Deen et al, 2023). This improvement in post-thaw quality is attributed to hydrogen bonding groups present in it and its ability to lower the phase transition temperature, which prevents crystal formation, thereby ensuring enhanced sperm integrity (Gastal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%